"Why do you ask?" the function of questions in institutional discourse - Freed, Alice F., 1946-; Ehrlich, Susan (Susan Lynn) (New York ; Oxford : Oxford University Press, 2010)
The act of questioning is the primary speech interaction between an institutional speaker and someone outside the institution. These roles dictate their language practices. This volume focuses solely on the question/answer process, drawing on a range of methodological approaches.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Oral communication; Questioning